The survival of bacterial pathogens during anaerobic sludge digestion - Yaziz, Mohammad Ismail (1980)
The value of domestic waste water sludge as a fertilizer and soil conditioner has made land disposal an attractive alternative to other methods of sludge disposal. There are three exceptions however for which the use of human wastes on pastures or folder crops can promote the transmission of diseases of significant public health or veterinary importance. These are:Beef tapeworm,Salmonellosis and Tuberculosis. This papaer reports on the survival of the Salmonella group of pathogens during anaerobic sludge digestion.